Multiorgan, Multimodality Imaging in Cardiometabolic Disease. (November 2017) - Kumar, Vidhya; Hsueh, Willa A.; Raman, Subha V.
Abstract : Cardiometabolic disease, spanning conditions such as obesity to type 2 diabetes mellitus with excess cardiovascular risk, represents a major public health burden. Advances in preclinical translational science point to potential targets across multiple organ systems for early intervention to improve cardiometabolic health. Validation in clinical trials and translation to care would benefit from in vivo diagnostic techniques that facilitate therapeutic advancements. This review provides a state-of-the-art, multimodality perspective spanning the multiple organ systems that contribute to cardiometabolic disease.